2006
DOI: 10.1093/ajcn/83.4.823
|View full text |Cite
|
Sign up to set email alerts
|

Oral glutamine and amino acid supplementation inhibit whole-body protein degradation in children with Duchenne muscular dystrophy

Abstract: Oral glutamine or amino acid supplementation over 10 d equally inhibits whole-body protein degradation in DMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 26 publications
0
36
1
6
Order By: Relevance
“…decrease in GSSG/GSH was associated with a reduction in MAPK (ERK1/2) phosphorylation. The antioxidant mechanism may explain our previous findings in DMD children demonstrating decreased whole body protein degradation after 5 h and 10 d Gln supplementation (6,7). This study is novel in describing a molecular basis for Gln's antiproteolytic effect in dystrophic muscle.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…decrease in GSSG/GSH was associated with a reduction in MAPK (ERK1/2) phosphorylation. The antioxidant mechanism may explain our previous findings in DMD children demonstrating decreased whole body protein degradation after 5 h and 10 d Gln supplementation (6,7). This study is novel in describing a molecular basis for Gln's antiproteolytic effect in dystrophic muscle.…”
Section: Discussionmentioning
confidence: 51%
“…Oxidative stress could contribute to muscle-wasting by regulating specific cell signaling pathways leading to increased proteolysis (5). We have shown that glutamine (Gln) supplementation decreases whole body protein breakdown in DMD children (6,7). However, the molecular basis for glutamine's antiproteolytic effect remains to be elucidated.…”
Section: Uchenne Muscular Dystrophy (Dmd) Is a Progressivementioning
confidence: 99%
“…Glutamine has shown little benefit towards improving strength, muscle mass, or function in limited human studies despite evidence of it slowing down whole-body protein degradation [17][18][19].…”
Section: Nutritional Statusmentioning
confidence: 99%
“…As it is a precursor to glutathione, supplementation with glutamine has also been shown to protect against oxidative stress in the mdx [436]. Several clinical studies and multicentre randomized placebocontrolled trials have been performed with glutamine [437][438][439]. Nutritional supplements have often been found to be more effective when administered in combination in the mdx [440][441][442].…”
Section: Free Radicals/rosmentioning
confidence: 99%
“…A combination of creatine and glutamine has also been therapeutically assessed in a Cooperative International Neuromuscular Research Group (CINRG) randomized controlled trial in DMD patients [445]. Glutamine has been reported to delay protein breakdown [437,438], but functional benefits were not observed in either trial [439,445]. Furthermore, a small clinical study of creatine alone only yielded modest improvements [446].…”
Section: Free Radicals/rosmentioning
confidence: 99%